2022
DOI: 10.1029/2022ja030680
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Ion Composition for Radiation Belt Modeling

Abstract: Electromagnetic ion cyclotron (EMIC) waves are important for the losses of relativistic electrons in the radiation belts by resonant wave-particle interactions (Thorne & Kennel, 1971). Doppler-shifted cyclotron resonance between EMIC waves and relativistic radiation belt electrons can lead to pitch-angle diffusion of the electrons and consequently losses from the belts. These interactions are believed to be responsible for several observational phenomena such as precipitating relativistic electrons (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 56 publications
3
12
0
Order By: Relevance
“…The results presented in this study could be a general reference for works on the cold ion populations. Although some of our results are consistent with previous findings (e.g., Ross et al., 2022), we can only get limited results about the cold ion populations and the ion compositions due to the small data set of the cold ion density comparable to the total electron density and the possible contaminations of helium and oxygen ion densities from cold protons. Further observational and simulation studies are desired to confirm the results presented in this study.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The results presented in this study could be a general reference for works on the cold ion populations. Although some of our results are consistent with previous findings (e.g., Ross et al., 2022), we can only get limited results about the cold ion populations and the ion compositions due to the small data set of the cold ion density comparable to the total electron density and the possible contaminations of helium and oxygen ion densities from cold protons. Further observational and simulation studies are desired to confirm the results presented in this study.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, Ross et al. (2022) emphasized the importance of ion composition on the decay of relativistic electron fluxes in the radiation belts by EMIC waves through kinetic simulations. They found that the radiation belt electron decay agrees better with Van Allen Probes observation when the helium fraction is only a few percent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2015) of the early Van Allen Probes era (2012–2014) suggest that O+ EMIC waves are found generally in the outer plasmasphere and occasionally the plasma trough which is the region in which this loss process is observed. In this region the O+ density can be higher than the partial ion compositions used here, thus increasing the strength of O+ band EMIC waves (e.g., Nosé et al., 2020; Ross et al., 2022). A study of Van Allen Probes data from 2012 to 2017 by H. Chen et al.…”
Section: Discussionmentioning
confidence: 85%
“…(2003) as used in our analysis presented here, have been used as limiting cases and storm time conditions for study of the sensitivity of minimum resonant energies and diffusion coefficients for ultrarelativistic electrons by Ross et al. (2022). The composition of Kersten et al.…”
Section: Discussionmentioning
confidence: 99%